EXPRESS: Common bile duct adenocarcinoma in a cat treated with surgical excision, choledochoduodenostomy and adjuvant toceranib phosphate - Qiao Ying Pauline Chan; Alen Lai (Journal of Feline Medicine and Surgery Open Reports, 2026)
Case summary A 2-year-old male neutered domestic shorthair cat was referred one month after medical management of extrahepatic biliary tract obstruction (EHBTO) for progressive lethargy and hyperbilirubinemia. Abdominal ultrasonography identified a 10mm obstructive common bile duct mass. The cat underwent common bile duct mass resection, choledochoduodenostomy and oesophagostomy tube placement, complicated by transient cardiac arrest. Histopathology confirmed biliary adenocarcinoma. Ongoing toceranib phosphate (toceranib) (2.44mg/kg PO Monday, Wednesday, Friday; 10mg PO Monday, Wednesday, Friday; Zoetis) was initiated 11 days postoperatively. Monitoring consisted of haematology, serum biochemistry, thoracic radiography, and abdominal ultrasonography. Follow‑up abdominal ultrasonography at 6 weeks, 14 weeks, and 10.5 months documented a pyloric mass, absence of ultrasonographic evidence of the pyloric lesion, and diffuse hepatic progression, respectively. Cytology of the pyloric mass and hepatic lesions confirmed carcinoma. Despite progression, the cat remained clinically well with normal serum total bilirubin, and continued toceranib postoperatively for 18 months. Relevance and novel information This report presents the first documented management of feline common bile duct adenocarcinoma combining surgical resection and oral toceranib, with objective assessment of treatment response. Toceranib therapy was ongoing 7.5 months after ultrasonographic disease progression, and the cat remained alive at that time, achieving a survival duration far exceeding previously reported median survival times for treated feline biliary carcinoma. Toceranib was well tolerated, with adverse effects limited to antiemetic-responsive nausea.